From Compliance to Cyber Resilience: Bridging Governance Gaps in Regulatory Cybersecurity Frameworks A Critical Analysis of Regulatory Evolution and Organizational Adaptation. (Architecture Image Studies, 2026)
The growth of regulatory cybersecurity systems across the globe has led to the development of a compliance-focused paradigm that, amid defining minimum security standards, frequently tends to overlook the adaptive, agile skills required of organisations to be cyber resilient. This paper will critically review the governance failures of compliance-based methods in cybersecurity and a new system of integrated governance that can accommodate both classic regulatory compliance and the principles of cyber resilience. With the assistance of a comparative analysis of the leading regulatory frameworks such as NIST CSF, ISO 27001, GDPR, NIS2 Directive, and DORA, and the analysis of high-profile cybersecurity incidents, we single out the systematic shortcomings in governance: checklist mentality, insufficient incident recovery procedures, ineffective accountability frameworks, and the lack of adaptive governance capabilities. The Cyber Resilience Governance Model we propose integrates compliance need with resilience concepts in four combined layers of governance, namely strategic, operational, and tactical and oversight with supporting continuous improvement mechanisms and cross-functional accountability frameworks. The framework fills in some critical gaps like adaptive risk management, organisational learning of incidents, supply chain resilience and human factors integration. The study is relevant to the body of research on cybersecurity governance in the sense that it offers both theoretical and practicable advice to policy makers, regulators, and organisational leaders who are in need of shifting their focus on reactive compliance to proactive resilience. These results are relevant to the corporate governance practices, regulatory design, and operationalisation of the cyber resilience of critical infrastructure areas.